The effect of fiber bleaching treatment on the properties of poly(lactic acid)/oil palm empty fruit bunch fiber composites - Rayung, Marwah; Ibrahim, Nor Azowa; Zainuddin, Norhazlin; Saad, Wan Zuhainis; Abdul Razak, Nur Inani; Chieng, Buong Woei (Multidisciplinary Digital Publishing Institute, 2014)
In this work, biodegradable composites from poly(lactic acid) (PLA) and oil palm empty fruit bunch (OPEFB) fiber were prepared by melt blending method. Prior to mixing, the fiber was modified through bleaching treatment using hydrogen peroxide. Bleached fiber composite showed an improvement in mechanical properties as compared to untreated fiber composite due to the enhanced fiber/matrix interfacial adhesion. Interestingly, fiber bleaching treatment also improved the physical appearance of the composite. The study was extended by blending the composites with commercially available masterbatch colorant.